The successful experience of gymnastics world champion coach: an interview analysis - Liu, Xiuxia; Weng, Xinghe; Qin, Huahui; Ma, Shuai; Wang, Guoqing (Frontiers in Psychology, 2024)
The role of a coach in enhancing athletes' performance and achieving success is welldocumented across numerous studies. However, the strategies employed by Chinese coaches in developing world champion gymnasts remain under explored. Methods: This research involved a single case study focusing on a coach from the Chinese National Men's Gymnastics Team, credited with nurturing eight world champion gymnasts.The inductive content analysis leads to that 6 subthemes, "international perspective and collaborative ability","ability to control and regulate training loads", "identifying athletes' needs and transforming them into motivation, "goal setting aligned with athletes' abilities", "adopting authoritative democratic coaching style" and "estabilishing hierarchical-style friendship"), and 3 themes, "training management and planning", "motivation and goal setting", "interpersonal communication" are manifested. An overarching theme "the successful experience of gymnastics world champion coach", is derived from the analysis. Conclusion: this research bridges the gap between theoretical knowledge and practical application, offering valuable insights into the successful experiences of gymnastics world champion coaches. The findings have the potential to influence coaching methodologies globally, fostering the development of resilient, motivated, and high-performing athletes. Future research should focus on sport-specific studies, longitudinal analyses, and cross-cultural comparisons to further advance the field of sports coaching and validate the effectiveness of these innovative coaching strategies.